Lacerated motherhood: mourning of mothers who have lost children in contexts of socio-political violence in Cali, Colombia - Mercado-Lenis, Diego Fernando (Prospectiva. Revista de Trabajo Social e Intervención Social, 2024)
The present study explored the grief experienced by mothers belonging to an association of victims in the city of Cali, Colombia, who lost their children in contexts of sociopolitical violence. To this end, a methodological strategy was implemented to understand the subjective elaboration of loss in these mothers, investigate the role played by sociocultural aspects in their grieving processes, and analyze the role of truth, reparation, and justice processes in their experience of loss. This qualitative methodological strategy employed a phenomenological design, resorted to convenience sampling, and conducted content analysis based on analysis categories. The strategy described by as ’research scenarios’ was employed to negotiate the researchers’ needs with those of the victim group, resulting in the conception of workshops with specific themes through which relevant information was obtained, namely: the reconstruction of mourning in connection with the participants’ biographies. The results highlighted several elements for understanding the uniqueness of this type of mourning, such as the necessity to resort to the notion of traumatic grief, given the senselessness of an experience impossible to process; the experience of a suffering body, broken by the detachment of the mother-child bond; the loss of fundamental trust in others contrasted with the communion experienced with other mothers and victims, becoming a powerful resilient element. Finally, the ineffectiveness of justice and the prevalence of impunity hindered the grieving process on one hand, but, on the other, facilitated the research setting to become a space where participants could provide testimony that was both reparative-healing.